Diagnostic Performance of Intestinal Fusobacterium nucleatum in Colorectal Cancer: A Meta-Analysis - Bo-Jian Peng (Chinese Medical Journal, 2018)
Background: Increasing evidence has supported the link of intestinal Fusobacterium nucleatum infection to colorectal cancer (CRC). However, the value of F. nucleatum as a biomarker in CRC detection has not been fully defined. In order to reduce the random error and bias of individual research, this meta-analysis aimed to evaluate the diagnostic performance of intestinal F. nucleatum in CRC patients and provide evidence-based data to clinical practice. Methods: An article search was performed from PubMed, Embase, Cochrane Library, and Web of Science databases up to December 2017, using the following key words: “Fusobacterium nucleatum”, ”Fusobacterium spp.”, ”Fn”, “colorectal cancer(s)”, “colorectal carcinoma(s)”, “colorectal neoplasm(s)”, and “colorectal tumor(s)”. Articles on relationships between F. nucleatum and CRC were selected according to the preestablished inclusion and exclusion criteria. This meta-analysis was performed using STATA 12.0 software, which included mapping of forest plots, heterogeneity tests, meta-regression, subgroup analysis, sensitivity analysis, and publication bias. The sensitivity, specificity, positive likelihood ratio (LR), negative LR, diagnostic odds ratio (DOR), and their corresponding 95% confidence interval (CI) of each eligible study were summarized. Results: Finally, data for 1198 participants (629 CRC and 569 healthy controls) in 10 controlled studies from seven articles were included. The summary receiver operator characteristic curve was mapped. The diagnostic performance of intestinal F. nucleatum infection on CRC was as follows: the area under the curve: 0.86 (95% CI: 0.83–0.89), the pooled sensitivity: 0.81 (95% CI: 0.64–0.91), specificity: 0.77 (95% CI: 0.59–0.89), and DOR: 14.00 (95% CI: 9.00–22.00). Conclusion: Intestinal F. nucleatum is a valuable marker for CRC diagnosis.